Prospects for Online Instructional Delivery Using Google Classrooms: Implications for Higher Education in Sub-Sahara Africa - Jumoke I. Oladele; Olawale S. Koledafe; Dorcas S. Daramola (Journal of Digital Learning and Education, 2021)
Technology is relevant in achieving educational development. Exploring how best to pattern and incorporate educational technology to engender sustainability remains relevant. It is against this backdrop that this study examined the Prospect of online instructional delivery in sub-Saharan African Universities using Google Classrooms ascertained concerning usability and accessibility while examining impending challenges. This study adopted a descriptive survey design. The study population was undergraduates enrolled at the University of Ilorin, Nigeria, a public institution owned by the Federal Government of Nigeria and the most soughed institution in terms of admission in the country. The target population was teacher trainees exposed to online instructional using Google Classrooms for 2018/2019 academic session. The study participants were purposively sampled; a total of 1933 participants. Data were gathered using a researcher designed questionnaire which was face and content validated. Three research questions were stated to examine accessibility, usability and challenges while the tested hypotheses were concerning prospects of Google Classroom for University of Ilorin undergraduates' learning across gender and departmental divides. Both descriptive statistics (Research Questions) and inferential statistics (Hypothesis) were employed in analysing data collected gathered. Significant findings revealed that Google Classroom holds prospects for innovative instructional approach for university undergraduates’ learning. However, there is a need to improve its level of accessibility to undergraduates to maximise its gains by making efforts to alleviate the challenges militating against smooth access to ensure sustainability in higher education in sub-Saharan Africa, apt in the current pandemic era.